Anafilaksi, çocuk, besin alerjsi, adrenalin oto-enjektörü - Pınar Yılmazbaş; Deniz Özçeker; Onur Adıgüzel; Özlem Terzi (Çocuk Dergisi)
Objective: Anaphylaxis is a systemic reaction that can be fatal if not treated quickly and correctly. The aim of our study is to share the demographic characteristics, clinical course and triggering factors of the cases diagnosed with anaphylaxis in the pediatric allergy outpatient clinic. Material and Method: The files of the cases with a diagnosis of anaphylaxis who were examined in the pediatric allergy outpatient clinic between the years 2017-2020, were evaluated retrospectively. Results: The average age of the 57 anaphylaxis cases included in our study was 7.8±4.5 years, 56.1% were male. Of the cases, 68.4% were atopic, 49.1% had elevated serum IgE levels and 36.8% were accompanied by eosinophilia. Triggering allergens were foods (40.4%), drugs (35.1%) and venom (5.3%) respectively. Mild anaphylaxis was observed in 64.9% of cases. It was observed that accompanying allergic diseases, asthma and presence of atopy increased the severity of anaphylaxis. Two or more anaphylaxis attacks were observed in nine cases. None of the cases, who were prescribed adrenaline auto-injector, used the adrenaline autoinjector during the attack. Conclusion: Anaphylaxis cases are more common in boys. The most common triggering factor is food. Asthma, concomitant allergic diseases and the presence of atopy are factors that increase the severity of attacks. Adrenaline auto-injector is not used in cases where it has been prescribed.